1901 S.C. Acts 748, no. 435, § 1 - (:unkn) unknown (General Publisher, 1901)
it shall be unlawful for any one to carry about the person whether concealed or not any pistol less than 20 inches long and 3 pounds in weight.
--
Keywords: CARRY